Effect of Addition of Palm Oil Empty Bunch Ash on Biogas Production from Palm Oil Mill Effluent - Clinton Velly Purwanto; Wagiman Wagiman; Jumeri Jumeri (Universitas Darussalam Gontor, 2023)
Palm oil mill effluent (POME) and empty palm fruit bunches (EPFB) are the waste with the largest amount of capacity resulting from the processing of the palm oil industry. POMEhas a high organic content that can be used as a biogas producer. This study used POME, EFB and cow dung as ingredients to produce biogas using an anaerobic batch digester with a volume of 20 liters, where each experiment had a different material composition and the addition of a different concentration of tankos ash solution. The purpose of this study was to determine the appropriate concentration of mixing a solution of tankos ash, POME, and cow dung in an effort to increase biogas production. The results showed that from several experiments that had been carried out during 30 days of observation, the experiment that had the highest value of biogas production and methane gas revenue was the experiment with a composition of 5 liters of cow dung, 5 liters of POMEand 10 liters of tankos ash solution (1:1:2) has a biogas production value of 58,646 ml and CH4 methane gas revenue of70.1%. It was concluded that the addition of tankos ash solution can significantly increase the pH of the waste digester and can increase the amount of biogas production with a certain concentration